Analysis of color image features extraction using texture methods - Aws AlQaisi; Mokhled AlTarawneh; Ziad A. Alqadi; Ahmad A. Sharadqah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A digital color images are the most important types of data currently being traded; they are used in many vital and important applications. Hence, the need for a small data representation of the image is an important issue. This paper will focus on analyzing different methods used to extract texture features for a color image. These features can be used as a primary key to identify and recognize the image. The proposed discrete wave equation DWE method of generating color image key will be presented, implemented and tested. This method showed that the percentage of reduction in the key size is 85% compared with other methods.